Aligning Goals for Certification and Professional Growth: Building Cooperation Among Bachelor of Education Programs in Alberta - Burns, Amy; Danyluk, Patricia; Nickel, Jodi; Kendrick, Astrid; Kapoyannis, Theodora; McNeilly, Elizabeth (Alberta Journal of Educational Research, 2022)
This article chronicles a provincial collaboration between ten Bachelor of Education degree-granting universities in Alberta, Canada. This collaboration focused on the newly implemented Teaching Quality Standard (2018) in Alberta and its impact on preservice teacher practicums. Data were collected through curriculum mapping and interviews at each institution. Each institution analyzed their own data and shared themes at a number of group meetings. Two common themes arose: (a) the interconnectedness of practicum and teacher education courses and (b) the role of the Teaching Quality Standard as a development tool within practicum. Key words: teacher education, practicum, teaching quality standard, postsecondary collaboration Cet article relate une collaboration provinciale entre dix universités de l'Alberta, au Canada, qui décernent des baccalauréats en éducation. Cette collaboration s'est concentrée sur la nouvelle norme de qualité de l'enseignement (2018) en Alberta et son impact sur les stages des enseignants en formation initiale. Les données ont été recueillies par le biais de la cartographie des programmes d'études et d'entretiens dans chaque établissement. Chaque établissement a analysé ses propres données et a partagé les thèmes lors de plusieurs réunions de groupe. Deux thèmes communs sont apparus : (a) l'interconnexion des stages et des cours de formation des enseignants et (b) le rôle de la norme de qualité de l'enseignement comme outil de développement dans le cadre des stages. Mots clés: formation des enseignants, stage, norme de qualité de l'enseignement, collaboration postsecondaire